Dampak Komitmen Organisasi Terhadap Kinerja Pegawai - Nicoline Hiariej; Gino Giovano Manuputty (Journal of Business Application, 2023)
Organizational commitment is still a problem for most organizations within a company. The problems that arise are basically very common in the field, for example to other companies. work discomfort or an offer from another company, so without hesitation the employee changes jobs. Desires that are not fulfilled will lead to negative attitudes due to the urge or desire not to come to work so that job satisfaction directly causes changes in employee performance. This study aims to determine whether organizational commitment affects employee performance at the Indonesian Christian University of Maluku (UKIM). The analysis used is simple regression to describe the effect of organizational commitment on employee performance. In collecting data, a questionnaire was used with a population of all UKIM administration employees and the sample was employees who had worked for more than 1 years.. The results of the analysis show that organizational commitment has a positive and significant impact on the performance of UKIM employees.